Measuring quality of life of people with predementia and dementia and their caregivers: a systematic review protocol. Issue 3 (30th March 2018) - Landeiro, Filipa; Walsh, Katie; Ghinai, Isaac; Mughal, Seher; Nye, Elsbeth; Wace, Helena; Roberts, Nia; Lecomte, Pascal; Wittenberg, Raphael; Wolstenholme, Jane; Handels, Ron; Roncancio-Diaz, Emilse; et al.
Abstract : Introduction: Dementia is the fastest growing major cause of disability globally and may have a profound impact on the health-related quality of life (HRQoL) of both the patient with dementia and those who care for them. This review aims to systematically identify and synthesise the measurements of HRQoL for people with, and their caregivers across the full spectrum of, dementia from its preceding stage of predementia to end of life. Methods and analysis: A systematic literature review was conducted in Medical Literature Analysis and Retrieval System Online, ExcerptaMedicadataBASE, Cochrane Database of Systematic Reviews, Cochrane Central Register of Controlled Trials, Database of Abstracts of Reviews of Effect, National Health Service Economic Evaluation Database and PsycINFO between January 1990 and the end of April 2017. Two reviewers will independently assess each study for inclusion and disagreements will be resolved by a third reviewer. Data will be extracted using a predefined data extraction form following best practice. Study quality will be assessed with the Effective Public Health Practice Project quality assessment tool. HRQoL measurements will be presented separately for people with dementia and caregivers by instrument used and, when possible, HRQoL will be reported by disease type and stage of the disease. Descriptive statistics of the results will be provided. A narrative synthesis of studies will also be provided discussing differences in HRQoL measurements by instrument used to estimate it, type of dementia and disease severity. Ethics and dissemination: This systematic literature review is exempt from ethics approval because the work is carried out on published documents. The findings of the review will be disseminated in a related peer-reviewed journal and presented at conferences. They will also contribute to the work developed in the Real World Outcomes across the Alzheimer's disease spectrum for better care: multimodal data access platform (ROADMAP). Trial registration number: CRD42017071416 .